Fc γ RIIA Genotypes and Its Association with Anti-C1q Autoantibodies in Lupus Nephritis (LN) Patients from Western India. (19th January 2010) - Pradhan, Vandana; Patwardhan, Manisha; Nadkarni, Anita; Ghosh, Kanjaksha
Abstract : To identify Fcγ RIIA genotypes in Systemic Lupus Erythematosus (SLE) patients and their association with anti-C1q antibodies. Methods . Fcγ RIIA genotyping was done in eighty Indian SLE patients and eighty healthy controls using allele-specific PCR. Anti-C1q antibodies were measured by ELISA. Results . LN patients showed higher SLEDAI (6–32) as compared to SLE patients without renal manifestations and had SLEDAI between 6–23. Fcγ RIIA polymorphic frequency in SLE patients was R131/H131 (67.5%), R131/R131 (20%) and H131/ H131 (12.5%) as against that of normal population (62.5%, 10%, and 27.5%), respectively. Sixty two patients (77.5%) showed positivity for anti-C1q antibodies. LN patients showed elevated levels of anti-C1q antibodies (258.2   u/ml ± 38 .5   U/mL ) as compared to SLE patients without nephritis (134.6 ± 24.6  U/mL). Among anti-C1q positive patients, 71% had R131/H131 genotype, 22.6% had R131/R131 and remaining 6.4%, patients had H131/H131 genotype. All anti-C1q positive patients with R131/R131 genotype had elevated levels of anti-C1q antibodies (>100 U/ml), whereas among anti-C1q negative patients, none had R131/R131 genotype. Conclusion . This first report on Indian SLE patients supports the hypothesis that Fcγ RIIA R131 variant over expression may constitute a susceptibility factor for development of severe SLE manifestations in LN patients.